Development and quality evaluation of apple pomace incorporated functional apple burfi - singh, Tanuja; Pathak, Vikas; Goswami, Meena (Indian Journal of Dairy Science, 2017)
The present study was carried out to evaluate the functional and nutritional properties of burfi prepared by incorporation of apple pomace at three different levels viz. 5, 10 and 15% and compared with control. The mean moisture and carbohydrate content increased in significant (p<0.05) manner while protein, fat, ash and total solid content decreased significantly (p<0.05) with increased level of apple pomace. The textural parameters i.e. hardness, adhesiveness, cohesiveness, gumminess and chewiness value decreased significantly but springiness increased in significant manner with apple pomace incoporation. Significant (p<0.05) difference in mean L* and a* values was recorded among treatments whereas mean b* values did not differ significantly. The mean L* value decreased and a* and b* value increased with the incorporation of apple pomace. The result of sensory parameters exhibited highest scores for T3 treatment for appearance and colour, texture, flavor and sweetness. The overall acceptability was highest for apple pomace burfi prepared with incorporation of 15% apple pomace.